Jejaring Kebijakan sebagai Strategi Inovasi Kebijakan Publik di Kabupaten Bandung - Rizky Ilhami (Pusat Riset dan Inovasi Nasional, 2025)
Public policy innovation is an important necessity for local governments in responding to the complexity of public issues. One relevant approach to encourage policy innovation is policy networks, which emphasize collaboration between government and non-government actors. This study aims to analyze the role of policy networks as a public policy innovation strategy in Bandung Regency. The study uses a qualitative approach with descriptive-analytical methods. Data were collected through in-depth interviews, observations, and documentation studies of actors involved in the public policy innovation process. The results show that public policy innovation in Bandung Regency is not yet fully supported by an inclusive and sustainable policy network. The dominance of the local government, weak coordination between actors, limited capacity of non-governmental actors, and regulatory and bureaucratic barriers are the main obstacles. This study emphasizes that strengthening collaborative, participatory, and institutionalized policy networks is an important prerequisite for promoting adaptive and sustainable public policy innovation at the local level.